Uji Beberapa Dosis Pseudomonas fluorescens untuk Pengendalian Penyakit Rebah Kecambah (Sclerotium rolfsii) Pada Bibit Cabe (PEST Tropical Journal, 2003)
The test of dosages of Pseudomonas fluorescensto control the damping-off caused Sclerotium rolfsii on pepper, Nasrun and Rustam. The experiment was conducted atLaboratory of The Assessment institute of Agricultural Technology and Screen houseof Food Crop Service of Riau Province from April to July 2003. The objective of theexperiment was to determine the best dosage of Pseudomonas fluorescensto con-trol the damping-off caused Sclerotium rolfsii on pepper. The experiment used ran-domized complete design with five treatment and five replications. The dosages ofPseudomonas fluorescens introduced to the soil were 0,5; 1; 2; 4 ml/1 and control.The results showed that the higher the dosage of Pseudomonas fluorescens intro-duced, the better effective to control the damping-off on pepper.